2021
DOI: 10.3390/ani11082276
|View full text |Cite
|
Sign up to set email alerts
|

Can Yucca schidigera Be Used to Enhance the Growth Performance, Nutrient Digestibility, Gut Histomorphology, Cecal Microflora, Carcass Characteristic, and Meat Quality of Commercial Broilers Raised under Tropical Conditions?

Abstract: This study aims to study the effect of Yucca shidigera as a phytobiotic supplementation in enhancing the production performance of commercial broilers reared under tropical environments. A total of 300 male day-old Ross 308 broiler chicks were randomly allocated into six treatment groups. Treatment 1 broilers were fed with commercial diets without antibiotics. Treatment 2 broilers were fed with commercial diets added with 100 mg/kg oxytetracycline antibiotic. Treatment 3, 4, 5, and 6 were fed with the same com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Supporting the idea, this study observed that T3 sheep fed with higher levels of B. decumbens tend to have greater feed leftover. This finding corroborates a study on saponin-containing plants ( Alghirani et al . 2021 ), where a decrease in feed intake was observed in animals fed diet supplemented with Yucca extract containing saponins.…”
Section: Discussionsupporting
confidence: 93%
“…Supporting the idea, this study observed that T3 sheep fed with higher levels of B. decumbens tend to have greater feed leftover. This finding corroborates a study on saponin-containing plants ( Alghirani et al . 2021 ), where a decrease in feed intake was observed in animals fed diet supplemented with Yucca extract containing saponins.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, Chen et al (2021), found that introducing yucca extracts to the diets of late gestating and lactating sows greatly increased DM digestibility. Contrary to our findings, Alghirani et al (2021) documented that the inclusion of yucca schidigera in broiler diets significantly lowered the digestibility of DM. According to Htoo et al (2007), a reduction in CP can lead to a decrease in AA digestibility, therefore adding YS and multi-carbohydrase might be the answer.…”
Section: Nutrient Digestibilitycontrasting
confidence: 99%
“…Yucca is rich in polyphenols, steroidal saponins and resveratrol, which was often used in food, cosmetics, pharmaceutical and animal feed as a solution or powder due to its properties of antioxidant, anti-inflammatory, antiviral, lowering cholesterol ( 22 ). The addition of yucca extract to feed can promote the growth performance of rabbits ( 7 ) and broilers ( 4 , 23 ). Additionally, the butyrate produced by C. butyricum is essential for the proper functioning of gut.…”
Section: Discussionmentioning
confidence: 99%